Periodontal therapy increases neutrophil extracellular trap degradation. Issue 5 (July 2020) - Moonen, Carolyn GJ; Buurma, Kirsten GD; Faruque, Mouri RJ; Balta, Maria G; Liefferink, Erol; Bizzarro, Sergio; Nicu, Elena A; Loos, Bruno G
In periodontitis, polymorphonuclear leucocytes (PMNs) are activated. They entrap and eliminate pathogens by releasing neutrophil extracellular traps (NETs). Abnormal NET degradation is part of a pro-inflammatory status, affecting co-morbidities such as cardiovascular disease. We aimed to investigate the ex vivo NET degradation capacity of plasma from periodontitis patients compared to controls (part 1) and to quantify NET degradation before and after periodontal therapy (part 2). Fresh NETs were obtained by stimulating blood-derived PMNs with phorbol 12-myristate 13-acetate. Plasma samples from untreated periodontitis patients and controls were incubated for 3 h onto freshly generated NETs (part 1). Similarly, for part 2, NET degradation was studied for 91 patients before and 3, 6 and 12 mo after non-surgical periodontal therapy with and without adjunctive systemic antibiotics. Finally, NET degradation was fluorospectrometrically quantified. NET degradation levels did not differ between periodontitis patients and controls, irrespective of subject-related background characteristics. NET degradation significantly increased from 65.6 ± 1.7% before periodontal treatment to 75.7 ± 1.2% at 3 mo post periodontal therapy, and this improvement was maintained at 6 and 12 mo, irrespective of systemic usage of antibiotics. Improved NET degradation after periodontitis treatment is another systemic biomarker reflecting a decreased pro-inflammatory status, which also contributes to an improved cardiovascular condition.